A systematic review on time trend incidence of rheumatoid arthritis in outpatient rheumatology clinics - van Delft, E. T. A. M.; Jamal, Maha; den Braanker, Hannah; Kuijper, T. M.; Hazes, J. M. W.; Lopes Barreto, Deirisa; Weel-Koenders, A. E. A. M. (Frontiers in Medicine, 2022)
Objectives: To classify patients with rheumatoid arthritis (RA) in an earlier stage of the disease, the ACR/EULAR classification criteria were updated in 2010. These criteria might have led to an increased incidence of RA in the rheumatology clinic. Since a higher incidence increases the socio-economic burden of RA, it is worthwhile to evaluate whether there is a time effect. Methods: A systematic review was conducted using Embase, Medline Ovid, Cochrane Central and Web of Science from database inception to February 2021. Included were only articles that addressed incidence rates of rheumatoid arthritis from rheumatology outpatient clinics. Results: Of the 6,289 publications only 243 publications on RA were found eligible for full-text review. Nine studies were included reporting incidence. The pooled incidence for RA was 11% (95% CI 6-16%) per year. Over time the incidence increased after the introduction of the 2010 ACR/EULAR classification criteria. Overall there was a high intragroup heterogeneity (I2=97.93%, p<0.001), caused by geographical area, study design and differences in case definitions. Conclusions: Although the incidence seems to increase after the introduction of the 2010 ACR/EULAR criteria, no conclusions can be drawn on this time effect due to heterogeneity.